DAMPAK HUBUNGAN SOSIAL PESERTA DIDIK YANG MENJADI KORBAN TINDAKAN BULLYING VERBAL DI SMP NEGERI 29 SAMARINDA - Alfira Sarah; Rury Muslifar; Wahyu Widyatmoko; Nuril Hidayanti (IKIP Siliwangi, 2026)
This study was initiated in response to a problem identified at SMP Negeri 29 Samarinda, East Kalimantan, where several students who were victims of verbal bullying experienced difficulties in establishing social relationships with their classmates. At this developmental stage, students should ideally be able to interact with peers to build meaningful relationships that may benefit them in the future. The purpose of this research is to explore the social impact experienced by students who are victims of verbal bullying. The study uses a qualitative descriptive approach. The primary informants consist of three female students, aged 14 years, from grades 9A, 9B, and 9C. Data collection was conducted through interviews involving the Guidance and Counseling teacher, homeroom teachers, class representatives, and the students themselves, along with observation and documentation. The data analysis technique employed an interactive model consisting of four stages: data reduction, data condensation, data display, and conclusion drawing. The research findings contained four themes, namely communication, peer social relations, social isolation, and cooperation. Keywords: Verbal Bullying, Social Relationships